Pliny’s Letters: tradition and originality of genre - Maciūnienė, Anna (Literatūra, 2007)
The publication consists of the first published translation of several Pliny’s Letters into Lithuanian, accompanied by an article which analyses questions of literature and rhetoric. The style of Pliny’s letters is light and elegant. He discusses literatures and rhetoric position, as well as juridical, economical and cultural systems. In Letters the author surveys educational situations in ancient Rome, makes a point about historical works and different political characters, gives advice on how to be a good orator. Pliny’s „Letters“ is a very important work in which it is possible to find all events and problems of the imperial Rome.